Effects of Gold Salt Speciation and Structure of Human and Bovine Serum Albumins on the Synthesis and Stability of Gold Nanostructures - Miranda, Érica G. A.; Tofanello, Aryane; Brito, Adrianne M. M.; Lopes, David M.; Albuquerque, Lindomar J. C.; de Castro, Carlos E.; Costa, Fanny N.; Giacomelli, Fernando C.; Ferreira, Fabio F.; Araújo-Chaves, Juliana C.; Nantes, Iseli L. (Frontiers in Chemistry, 2016)
The present study aimed to investigate the influence of albumin structure and gold speciation on the synthesis of gold nanoparticles (GNPs). The strategy of synthesis was the addition of HAuCl4 solutions at different pH values (3-12) to solutions of human and bovine serum albumins (HSA and BSA) at the same corresponding pH values. Different pH values influence the GNP synthesis due to gold speciation. Besides the inherent effect of pH on the native structure of albumins, the use N-ethylmaleimide (NEM)-treated and heat-denaturated forms of HSA and BSA provided additional insights about the influence of protein structure, net charge, and thiol group approachability on the GNP synthesis. NEM treatment, heating, and the extreme values of pH promoted loss of the native albumin structure. The formation of GNPs indicated by the appearance of surface plasmon resonance (SPR) bands became detectable from fifteen days of the synthesis processes that were carried out with native, NEM-treated and heat-denaturated forms of HSA and BSA, exclusively at pH 6 and 7. After two months of incubation, SPR band was also detected for all synthesis carried out at pH 8.0. The mean values of the hydrodynamic radius (RH) were 24 and 34 nm for GNPs synthesized with native HSA and BSA, respectively. X-ray diffraction (XRD) revealed crystallites of 13 nm. RH, XRD, and zeta potential values were consistent with GNP capping by the albumins. However, the GNPs produced with NEM-treated and heat-denaturated albumins exhibited loss of protein capping by lowering the ionic strength. This result suggests a significant contribution of non-electrostatic interactions of albumins with the GNP surface, in these conditions. The denaturation of proteins exposes hydrophobic groups to the solvent, and these groups could interact with the gold surface. In these conditions, the thiol blockage or oxidation, the latter probably favored upon heating, impaired the formation of a stable capping by thiol coordination with the gold surface. Therefore, the cysteine side chain of albumins is important for the colloidal stabilization of GNPs rather than as the reducing agent for the synthesis. Despite the presence of more reactive gold species at more acidic pH values, i.e., below